The Influence of Liquidity, Profitability and Leverage on Financial Distress Conditions in State-Owned Banks Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Yulistiyani; Basrowi; Rani Sri Sumarsih; Muhammad Faqih C M; Bambang M. Saputra; M Faqih Chairurrijal M; Awal Ramdan; Priyaartharshini Chandrasekaran; Herley Jaubin; Gie Anne D Viado (Southeast Asian Journal of Science and Technology, 2024)
Financial distress is a stage of decline in a company's financial condition that occurs before bankruptcy. This research aims to determine the effect of liquidity, profitability, and leverage on financial distress conditions in state-owned banks listed on the IDX for the 2019-2023 period. This research used a sample of 4 companies with a total of 80 financial reports researched. The sampling technique uses a saturated sample technique or uses the entire existing population. The data analysis method in this research uses the multiple linear regression analysis method. The data was processed using SPSS version 27. The results show that partial Liquidity (CR) has a positive and significant effect, Profitability (ROA) has a positive and significant effect, and Leverage (DAR) has no effect and is not significant on Financial Distress conditions. Simultaneously Liquidity, Profitability, and Leverage have a significant effect on Financial Distress conditions.